PENERAPAN RESTORATIVE JUSTICE DALAM PENYELESIAN TINDAK PIDANA YANG DILAKUKAN OLEH ANAK YANG BERMASALAH DENGAN HUKUM MENURUT UNDANG-UNDANG RI NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Johannes Gajahmada Siregar (Iustitia Omnibus (Jurnal Ilmu Hukum), 2020)
ABSTRACT Restorative Justice is another way of criminal justice that promotes the approach of humanism on the one hand and victims and society on the other hand, as a manifestation of seeking and returning to a pattern of good relations. This process is done through discretion (policy) and diversion, namely the transfer from the criminal justice process to the non-formal process through deliberation. In other words, Child Crimes who are dealing with the law, in the era of legal protection and protection of human rights (HAM), are regulated in Law Number 11 of 2012 on the Juvenile Justice System (UUSPPA), attached to Restorative justice and diversion. In addition, it is also regulated in Law Number 31 of 2014 on the Protection of Witnesses and Victims, as well as Law Number 35 of 2014 on Child Protection. The formulation of the issues concerning the implementation of the SPPA Law, namely how is the application of Restorative Justice on child crime, the readiness of law enforcers, and related institutions, the next, how is the system of punishment and action, and how is the model and concept of protection against the Implementation of Restorative Justice on Child Crime. In this study, researchers used the method of Juridical Normative approach that by analyzing the articles of legislation related to the problems studied. The nature of the research is descriptive analysis, namely to provide as much data as possible about the conditions or symptoms that become the object of research. The research stages are literature study to obtain secondary data derived from primary legal material, secondary law material, tertiary legal material, and through field research, is data analysis without using formulas and figures. The results show that, in the implementation of the criminal justice system of children, in Indonesia, still faces various problems. Existing issues include detention of children who are not in accordance with the procedure, the long trial process ranging from investigations, prosecutions, courts, which ultimately put the convicted child in a penitentiary or returned to society with free judgment, will still leave trauma and negative implications on children. Based on the data obtained, the crime of children in Bandung City in 2017 amounted to 364 cases. Is Needed to know more about the implementation of Diversion and Restorative Justice against child offenders at the investigation stage in Bandung City Diversions, usually, are done in cases of minor crimes or cases of torture or theft. However, for cases of abuse or drugs are all delegated. However, usually, if the perpetrators of children, should be pursued peace. Peace, usually, is advised by the investigator, held first with legal experts in the Police and its decisions are taken in a meeting and usually there is no grace period for how long the peace process will take. However, sometimes in carrying out its duties, the police do not even offer diversion and restorative justice. In addition, the victim's family is also not willing to make peace marked by a statement on the stamp duty that asks the perpetrator to be extremely punished. Based on the findings in the field, the maximum diversion and restorative justice is not done because officials’ lack of the ability of the to understand the concept, so in its application it is rarely done, except the family of the victim or family of the perpetrator who do the peace outside the police.